PENDAMPINGAN MANAJEMEN KEUANGAN PONDOK PESANTREN AL-MUSTAQIM LUMAJANG - Roshiful Aqli Qosyim (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
The article describes financial management assistance at the Al-Mustaqim Lumajang Islamic Boarding School. The research uses a constructive method. Based on the results of the research, financial management assistance at the Al-Mustaqim Lumajang Islamic Boarding School has carried out the following activities: financial management at the Al-Mustaqim Lumajang Islamic boarding school is carried out through a systematic process, starting with preparation assistance, assistance in developing the Islamic Boarding School Income Budget Plan, mentoring receipt and disbursement of pesantren funds. The supervision system for the Al-Mustaqim Lumajang Islamic boarding school is carried out through evaluation and accountability.